Madidihang with a Social and Economic Domain Approach in Talaud Regency (Agrikan Jurnal Agribisnis Perikanan, 2024)
Fishing for yellowfin tuna has been carried out by fishermen for the last 10 (ten) years, where fishing for yellowfin tuna has been carried out continuously, which can cause fishing activities to be environmentally unfriendly and have an impact on reducing the production of fish catches.This research aim to determine the value and status of sustainability of yellowfin tuna fishing in talaud islands district, using an ecosystem approach to fisheries management social domain and economic domain. The research method is descriptive. The research sampling technique used purposive sampling technique. The social domain is very good and economic domain is good.
Keywords: Yellowfin tuna; Social domain; Economic domain